Attention Deficit Hyperactivity Disorder in Children and Adolescents - Banerjee, Somnath (IntechOpen, 2013)
ADHD in children and adolescents is a neurodevelopmental disorder, which is recognized by the clinicians all over the world. ADHD is a clinical diagnosis based on reliable history, reports from home and school and a physical examination to rule out any other underlying medical conditions. ADHD can cause low self-esteem in the child and impair quality of life for the child and the family. It is known that ADHD is a chronic illness and that clinicians needed to use chronic illness principles in treating it. The last 10 years have seen an increase in the number of medications that have been approved for the treatment of ADHD. This book has tried to address some of the issues in ADHD.